Personnel Management of Village Officials Through SIMPEG Application in Realizing Village SDGs in Kendal Village, Sekaran District, Lamongan Regency - Noviyanti; Isbandono, Prasetyo; Utami, Dian Arlupi; Wibisono, Haryo Kunto; Rosdiana, Weni (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe and analyze the personnel management of village officials by developing SIMPEG application to realize Sustainable Development Goals (SDGs) of Village in Kendal Village, Sekaran District, Lamongan Regency. The type of research is research dan development (R&D) method by using prototype model that consists of 3 steps, which are: listen to customer, build/revise mock-up, and customer test drives mock-up. The techniques of data collection are literature study, deep interview, observation, and documentation. The results show that the personnel management using SIMPEG application has realized the 17th SDGs of Village (partnership for rural development through management and integration of information and communication technology (ICT). The development of Village SIMPEG application also is one of the efforts to realize the principles of electronic government and orderly personnel administration. However, this application still needs develpment by providing upload button to upload files related to several SIMPEG menu. The upload button can be used as an electronic archive that support information, such as educational history form, training history form, and award history form